Karakterisasi Dan Hubungan Kekerabatan 15 Genotipe Tanaman Cabai (Capsicum annuum l.) Yang Ditanam di Lahan Gambut - Situmorang, Holida Sari; Zuhry, Elza; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aim is to determine the characteristics of genotypes of chili and to leard the genetic relationship between the tested genotypes on peatlands. This research lasted from January to June 2013 in peatland experimental garden, Agriculture Faculty, University of Riau, Rimbo Panjang Village, Tambang district Kampar regency. The experimental design used was randomized block design which is consist by 15 treatment with three replications then obtained 24 units of the experiment. There are two parameters observed on this research, quantitative and qualitative parameters. Qualitative parameters analyzed statistically by using analysis of variance, followed by Duncan New Multiple Range Test (DNMRT) at the level of 5%, meanwhile qualitative parameters used for Cluster Analysis referring to Descriptor For Capsicum (IPGRI). Results showed that there are 15 genotypes of chilli differences and similarities based on quantitative and qualitative parameters. The genetic relationship from tested genotypes seen in the qualitative parameters (number of flower per axil, corolla colour, corolla spot colour, filament colour, corolla shape, fruit colour intermediate phase, fruit shape, fruit point shape and the structure of fruit point shape). Keyword : Capsicum annuum L, peatland, characterization, Cluster Analysis